Analysis of Λ b 0 $$ Λ_b^0 $$ → pK − μ + μ − decays - The LHCb collaboration; R. Aaij; A. S. W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A. A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C. A. Aidala; et al. (Journal of High Energy Physics)
Abstract The differential branching fraction and angular coefficients of Λ b 0 $$ Λ_b^0 $$ → pK − μ + μ − decays are measured in bins of the dimuon mass squared and dihadron mass. The analysis is performed using a data set corresponding to 9 fb −1 of integrated luminosity collected with the LHCb detector between 2011 and 2018. The data are consistent with receiving contributions from a mixture of Λ resonances with different spin-parity quantum numbers. The angular coefficients show a pattern of vector-axial vector interference that is a characteristic of the type of flavour-changing neutral-current transition relevant for these decays.